A multicentre pharmacoepidemiological study of dermatological disorders in Wardha district - Yuwnate, Anita H.; Chandane, Rakhamaji D.; Giri, Kiran R.; Yunati, Monica S.; Sirsam, Shyam S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Skin diseases are common among the general population and account for a high percentage of all diseases. For considering the increase in the prevalence of specific skin diseases, prevalence data are needed. Appropriate treatment of common diseases and provision of essential drugs are two essential components of the primary health care. The aim in dermatological therapy is to use the safest and least number of drugs in order to obtain the best possible effect in the shortest period at reasonable cost. For that important step is taken to monitor, evaluate and therapeutically analyze the prescribing pattern of dermatological drugs. Methods: 12210 cases were screened for dermatological disorders in the Primary Health Care Centers and Rural Hospital of Wardha district during the time frame 1st January 2006 to 30th September 2010, out of which 1000 patients experienced different variety of dermatological disorders were analyzed. In prescription analysis 800 prescriptions with 1946 drugs were analyzed. Results: The prevalence of dermatological disorders in our study was found 8.19%. Out of 1000 patients, there were 567 females (56.7%) and 433 male (43.3%).1000 cases were divided into five age groups viz. 1-20 yrs, 21-40 yrs, 41-60 yrs, 61-80 yrs and more than 80 yrs. Percentage distribution for the various age ranges were 21%, 48%, 20%, 8% and 3% respectively. In spectrum of dermatological disorders, Acne vulgaris (14.8%) was the most common disorder followed by Tinea infection (13.6%) , Eczema (13.2%), scabies (12.4%) and pyoderma (11.6%), Acute urticaria (6.6%), Melasma (5.8%), Psoriasis (3.8%), Polymorphous light eruption (3.6%), Phytophotodermatitis (2.6%), Leprosy (2%) and other disorders (10%). The total number of drugs prescribed in 800 prescriptions was 1946 i.e. on average 2.43 drugs were prescribed per patient. Out of 1946 drugs, 1054 were topical and 892 were oral preparations. Antifungal was most common topically prescribed drug. Conclusions: The prevalence of dermatological disorders is 8.19 %. Younger age group (21-40 yrs) and Females is most affected by dermatological disorders. The commonest dermatological disorder is Acne and in prescription analysis, antifungals are most commonly prescribed.